Porous Silicon Antireflective Coatings for Silicon Solar Cells - Mouafki Α. Μ.; Bouaïcha, F.; Hedibi, A.; Gueddim, A. (Engineering, Technology & Applied Science Research, 2022)
This study presents a numerical investigation of the reflectivity of a Single Anti-Reflective Layer (SARL) and a stack of antireflective layers made of porous silicon. The stack consists of a certain number of periods, and each period contains two layers with different porosity. The simulations were conducted using the well-known Stratified Medium Theory (SMT) framework and the effect of porosity was studied. The optimal value was determined at 60% for the SARL and 65/55% for the stack of 12 periods and 6 layers. The angle of incidence was found to have more influence on the stack reflection than on the SARL reflection. The results of this investigation show that porous silicon can be used as an effective anti-reflective coating for silicon solar cells.